Situación actual de la comercialización del cultivo de piña (Ananas comosus) en el Ecuador - Muñoz Mora, Nayely Michel (2023)
Pineapple marketing in Ecuador is directly related to the export of 85% of production to foreign markets, while the rest is destined for domestic consumption; high freight costs and shortage of containers prevent the transfer to other regions of the country, generating a surplus in the domestic market where supply is growing and prices are declining. The information was collected through the technique of analysis, synthesis and summary in order to inform the reader about the current situation of the commercialization of pineapple (A. comosus) in Ecuador. From the above, it was determined that the commercialization of pineapple in the local market is a process that represents a sequence of stages and distribution such as: farmer, collector, wholesaler, retailer, consumer. The quality of the fruit must comply with various parameters that may vary depending on the market, in which activities such as washing the fruit, packaging and transporting the fruit must be carried out. Wholesale pineapple prices have a very spontaneous variation due to many factors, either in the harvest or in production; locally the average price of pineapple is $ 0.85 per unit. The production of a producer per hectare is around 25,000 kilos of pineapple, which is sold at a price of $ 0.35, which gives an income of $ 8,750; from this income the producer covers production costs and returns the initial investment. The different distribution channels of the pineapple exporting companies are the same as those used by the banana companies, which take advantage of the transportation logistics that exist for export. The commercialization of pineapple in the international market is a process that represents a direct relationship between the farmer and the exporter and then the final consumer.